Apprendre à enseigner en « classe intégrée » au sein d’un établissement scolaire régulier : des stagiaires genevois décrivent et commentent leur activité - Coralie Delorme (Recherches en Éducation)
The aim of this article is to describe how students enrolled in special-education teacher vocational training perceive the complexity of supporting the learning of pupils with special educational needs as they learn to teach in a special education class integrated into a mainstream primary school. A qualitative study carried out in Geneva (Switzerland) with three trainees enabled us to gain access to their activity in a training situation, during a teaching session conducted in this context. The data were obtained from recording video recordings of the trainees teaching, and by trainees’ confronting with this film of their activity during filmed self-confrontation interviews. The results reveal the difficulties specific to student-trainees when learning to teach in an integrated classroom. They underline the importance of producing knowledge that can be reused in the vocational training of special teachers.